THE IMPACT OF NURSE-LED CARE COORDINATION PROGRAMS ON REDUCING HEALTHCARE COSTS - Nasser Majed Ali Aldawsari, Salem Mohammed Saed Almlali, Turki Faisal Alharbi, Mody Nasser Alkamis, Latifa Abdullah Al-Jouraid, Mubarak Ibrahim Mohammed Alsaeed, Fatama Said Alqahtani, Maram Hameed Albishi, Alia Matar Alanazi, ,; Faiz Ahmed Alasmari, Fahad Ali Albahli, Halimah Ahmad Hussin Alnami, Nemh Ahmed Rajhi, Zahrah Saleh Ahmad Bubshait, Elyas Ameer Alghasham, (Chelonian Research Foundation, 2022)
A significant number of individuals over the globe possess intricate health and social care requirements. Ensuring care coordination for these patients is an essential aspect of integrated care and a basic obligation of primary healthcare. Registered nurses have a significant role in coordinating care. This study builds upon existing theoretical research and presents a comprehensive analysis of care coordination treatments used by nurses for complicated patient populations in primary healthcare settings. We conducted a methodical search throughout the databases CINAHL, MEDLINE, Scopus, and ProQuest. The nursing care coordination activities were consolidated into three distinct categories: interventions aimed at the patient, family, and caregivers; interventions aimed at health and social care teams; and interventions aimed at facilitating collaboration between patients and professionals. Interpersonal communication and information transmission have been identified as fundamental behaviors that facilitate all other activities. These factors include heightened levels and regularity of activities, consistent care relationships, and visits to the individual's residence. Given the increasing intricacy of patients' requirements, it is crucial to focus on empowering primary healthcare to properly fulfill its significant position in coordinating treatment. This involves identifying primary care employment models that would promote interdisciplinary collaboration and the provision of integrated care, while ensuring the provision of intense but efficient coordinated care. Keywords: care coordination, integrated care, primary healthcare, complicated health and social care requirements, registered nurses, review